2014
DOI: 10.1111/pbi.12231
|View full text |Cite
|
Sign up to set email alerts
|

Gluten quality of bread wheat is associated with activity of RabD GTPases

Abstract: In the developing endosperm of bread wheat (Triticum aestivum), seed storage proteins are produced on the rough endoplasmic reticulum (ER) and transported to protein bodies, specialized vacuoles for the storage of protein. The functionally important gluten proteins of wheat are transported by two distinct routes to the protein bodies where they are stored: vesicles that bud directly off the ER and transport through the Golgi. However, little is known about the processing of glutenin and gliadin proteins during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
1
10
0
1
Order By: Relevance
“…Analyses of sequence similarities and of the presence of specific family and subfamily conserved motifs in their sequence allowed the identification of the closest homologues from Arabidopsis and the assignment of these sequences to members of the Rab family. The Rab sequences do not cluster in a species specific manner but rather within subfamilies supporting the findings of previous authors [41,46]. According to these authors, it can be speculated that the members of the same cluster display similar functions.…”
Section: Figsupporting
confidence: 87%
See 1 more Smart Citation
“…Analyses of sequence similarities and of the presence of specific family and subfamily conserved motifs in their sequence allowed the identification of the closest homologues from Arabidopsis and the assignment of these sequences to members of the Rab family. The Rab sequences do not cluster in a species specific manner but rather within subfamilies supporting the findings of previous authors [41,46]. According to these authors, it can be speculated that the members of the same cluster display similar functions.…”
Section: Figsupporting
confidence: 87%
“…Comparison between the 'CK' and the 'P' group at the same ripening stage (unripe or ripe stage) revealed significantly higher levels in the 'P' group. Evidence from wheat has shown that transgenic lines with down-regulated RabD gene resulted in grains with altered bread making quality [46]. These authors suggested that the reduced bread making quality observed in the transgenic grains might have been due to the altered trafficking of the gluten proteins.…”
Section: Figmentioning
confidence: 99%
“…The RABA family of genes is widespread across a range of plant phyla including wheat, rice and maize [29,30]. Thus, lines in which activities of the RABA4 orthologues in these species have been inhibited may have considerable commercial relevance, especially considering the additional fact that these genetic modifications do not appear to adversely impact on the yield of biomass or its total glucose content.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has also observed very low expression of other regulatory genes related to protein trafficking throughout the seed development (Rab GTPases), indicating their improper regulation under stress conditions. Tyler et al (2015) also showed decreased expression of Rab GTPases under heat stress, thus stopping the regulation of vesicles carrying seed storage proteins from endoplasmic reticulum to Golgi complex. To sum up, heat stress has enhanced various stress-responsive genes and proteins but cannot maintain their expression under prolonged stress duration.…”
Section: Effect Of Heat Stress On the Stress Responsementioning
confidence: 99%